2003
DOI: 10.1096/fj.03-0322
|View full text |Cite
|
Sign up to set email alerts
|

Imatinib induces mitochondria‐dependent apoptosis of the Bcr‐Abl‐positive K562 cell line and its differentiation toward the erythroid lineage 1

Abstract: Imatinib has emerged as the lead compound for clinical development against chronic myeloid leukemia. Imatinib inhibits the kinase activity of Bcr-Abl, which functions by enhancing the proliferation of hematopoietic precursors and protecting them against apoptosis. Imatinib induces apoptosis of Bcr-Abl positive cells, but how the drug effectively kills these cells remains partially understood. We show here that in K562 cells imatinib i) abolished Bcr-Abl phosphorylation and activity and as a consequence Erk1/2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
75
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 53 publications
11
75
0
Order By: Relevance
“…The phosphorylation status of these kinases is thought to represent a reliable index of their activity (Herrant et al, 2002). In the absence of PMA, the significant activation of Erk1/2 can be explained by the presence in these cells of the constitutively activated Bcr-Abl chimaeric protein (Jacquel et al, 2003) (Figure 4b). PMA was found to stimulate phosphorylation of Erk1/2, JNK and Akt at 30 min, an effect maintained for approximately 6 h, but inhibit p38 MAPK phosphorylation after 2 h of treatment ( Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphorylation status of these kinases is thought to represent a reliable index of their activity (Herrant et al, 2002). In the absence of PMA, the significant activation of Erk1/2 can be explained by the presence in these cells of the constitutively activated Bcr-Abl chimaeric protein (Jacquel et al, 2003) (Figure 4b). PMA was found to stimulate phosphorylation of Erk1/2, JNK and Akt at 30 min, an effect maintained for approximately 6 h, but inhibit p38 MAPK phosphorylation after 2 h of treatment ( Figure 4b).…”
Section: Resultsmentioning
confidence: 99%
“…K562 cells can undergo further differentiation in both megakaryocytic and erythroid lineages depending on the stimulus. Phorbol esters such as PMA-stimulated megakaryocytic differentiation (Shelly et al, 1998;Kim et al, 2001;Dorsey et al, 2002;Pettiford and Herbst, 2003), whereas hemin, hydroxyurea, Ara-C or as reported more recently imatinib mesylate (gleevec) induced erythroid differentiation of this cell line (Belhacene et al, 1998;Park et al, 2001;Jacquel et al, 2003;Kawano et al, 2004a, b). Megakaryocytic differentiation of K562 cells induced by PMA mimics, in part, the physiologic process that takes place in the bone marrow in response to a variety of stimuli (Long et al, 1990).…”
Section: Introductionmentioning
confidence: 82%
“…After 48 and 72 h in the presence of the drugs, XTT metabolism dropped to only 30 and 20%, respectively, and ZVAD-fmk was found to increase cell metabolism significantly to approximatively 50% (Figure 2b- judged by RT-PCR analysis of erythroid markers (Jacquel et al, 2003;Jacquel et al, 2006). We took advantage of this property to analyse the effect of SB202190 on imatinib-mediated apoptosis and erythroid differentiation using flow cytometry.…”
Section: Bcr-abl Inhibitors Induced Caspase Activation and Cell Deathmentioning
confidence: 99%
“…Following drug treatment, the Bcr-Abl protein is rapidly dephosphorylated and inactivated, leading to the blocking of the above-mentioned signaling cascades. Subsequently, the cell cycle progression is impaired and cells undergo an apoptotic programme characterized by activation of caspases 9, 8 and 3 (Jacquel et al, 2003). Furthermore, it has been recently shown that inhibition of caspases in imatinib-treated K562 cells shifted the cells from a caspase-dependent to a necrosis-like cell death process, suggesting that imatinib also triggered caspase-independent cell death (CID) (Okada et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation